A case of organophosphate induced delayed motor neuropathy without any sensory involvement - Mainul Hasan Chowdhury, Mohammad; Masum, Abdullah; Kawnayn, Ghulam; Mohammad Khurshid, Husain; Rezeul Huq, Muhammad; Tuj Zohura, Fatima (BIRDEM Medical Journal, 2024)
Organophosphate induced delayed neuropathy is a sensory-motor distal axonopathy that usually occurs after ingestion of certain organophosphate compound. It is usually characterized by distal degeneration of axons of peripheral nervous systems, predominantly in lower limbs and occurs within 2–6 weeks after exposure. Clinical features include cramping muscle pain, distal numbness, paresthesia, followed by progressive weakness and loss of deep tendon reflexes in affected limbs. Electrophysiological studies reveal a motor axonal neuropathy characterized by reduced amplitude of the compound muscle potential and normal or reduced nerve conduction velocities. We report a case of 29-year-old male patient who developed progressive lower limbs weakness over four weeks after ingestion of chlorpyrifos based insecticide. His nerve conduction study revealed motor axonal neuropathy without any sensory involvement affecting both lower limbs. BIRDEM Med J 2024; 14(1): 49-52